2022
DOI: 10.14336/ad.2021.1208
|View full text |Cite
|
Sign up to set email alerts
|

Common Pathogenetic Mechanisms Underlying Aging and Tumor and Means of Interventions

Abstract: Recently, there has been an increase in the incidence of malignant tumors among the older population. Moreover, there is an association between aging and cancer. During the process of senescence, the human body suffers from a series of imbalances, which have been shown to further accelerate aging, trigger tumorigenesis, and facilitate cancer progression. Therefore, exploring the junctions of aging and cancer and searching for novel methods to restore the junctions is of great importance to intervene against ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 346 publications
1
11
0
Order By: Relevance
“…Recent studies indicate that aging is accompanied by progressive epigenetic alterations in both dividing and nondividing cells [55], with epigenetic changes proposed as a hallmark of aging by 2023 [56]. Aging is a risk factor for various age-related diseases, including cancers [57][58][59][60] and degenerative diseases [61][62][63][64]. Our study found that ALYREF expression was significantly related to aging, confirming the link between epigenomics, aging, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that aging is accompanied by progressive epigenetic alterations in both dividing and nondividing cells [55], with epigenetic changes proposed as a hallmark of aging by 2023 [56]. Aging is a risk factor for various age-related diseases, including cancers [57][58][59][60] and degenerative diseases [61][62][63][64]. Our study found that ALYREF expression was significantly related to aging, confirming the link between epigenomics, aging, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These included: (1) molecular biomarker for preoperative evaluation: surgeons can further assess the practical value of SKA3 as a molecular biomarker before surgery, exploring its potential as a predictive indicator for patient prognosis and surgical selection; (2) practical impact on surgical outcomes: surgeons can conduct a more in-depth analysis of how SKA3 overexpression affects surgical outcomes, such as postoperative survival, tumor clearance, and postsurgery monitoring, which might contributed to establishing a direct link between research findings and practical implications in surgical practice; (3) clinical application prospects: in the future, surgeons might improve patient prognosis through therapeutic interventions targeting SKA3 and the practical prospects of implementing these interventions in surgical treatments. In addition, the relationship between aging and cancer susceptibility has been extensively documented, with older individuals demonstrating a higher likelihood of developing malignant tumors compared to their younger counterparts 105 110 . As the global population ages, a surge in cancer incidence is projected over the next few decades 102 , 111 .…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…Exposure of PCa to therapies targeting AR, different anticancer compounds, and ionizing radiation can induce a senescent phenotype, termed therapy-induced senescence (TIS) ( 65 ). The shared mechanisms of senescence and PCa encompass disruptions in proteostasis, dysbiosis of the microbiota, persistent chronic inflammation, and widespread immunosenescence ( 66 ). TIS may benefit patients in the treatment of PCa ( 67 ).…”
Section: Resistance To Androgen Deprivation Therapy (Adt) and Cell Se...mentioning
confidence: 99%